PENGEMBANGAN DESAIN PESAN BERBASIS PLATFORM NEARPOD PADA MATA PELAJARAN IPA UNTUK SISWA KELAS VII SMP - Rahmi Ismah; Zuliarni (GoAcademica Research dan Publishing, 2022)
The development of a message design based on the Nearpod platform is an effort to convey learning messages in the learning process and make students feel different learning experiences so that they can increase students' enthusiasm in participating in learning. The purpose of this study was to develop a message design using the Nearpod platform in science subjects for grade VII junior high school students and to determine the validation, practicality and effectiveness of the product developed so that it was valid and feasible to use. This type of development research is Research and Development (R&D), using the ADDIE model. The validity test was carried out by three validators, namely two media validators and one material validator. Practicality and effectiveness tests were conducted on 27 students of class VII.B at State Junior School 1 Enam Lingkung. The results of the research from the development of the Nearpod platform-based message design in science subjects, obtained the results of media validation from two media validators categorized as